Menyentuh Surga, Memeluk Dunia: Sebuah Proposal Konstruktif untuk Liturgi Reformed yang Eskatologis-Misional - Timotius Verdino (Asosiasi Teolog Indonesia, 2016)
In and since its historical beginnings, Christian worship has retained its eschatological dimension, as this even is intricately related to aspects of its missionality. As such, the worship given and performed in the contemporary Reformed church must also retain its eschatological-missionality. While Martha L. Moore-Keish locates this eschatological dimension within the event of Holy Communion, Reformed churches do not celebrate Holy Communion every Sunday. Might Reformed worship, whenever it goes without Holy Communion, be losing its very own eschatological quality? This article serves as a constructive proposal for (re)locating the eschatological-missionality of weekly Reformed worship, by way of emphasizing the eucharistic aspect of the Reformed liturgy. To pursue this inquiry, the present article undertakes an investigation of Reformed eucharistic theology, followed by a consideration of the Orthodox Alexander Schmemann's figuring of the world as sacrament and its relation to mission. I then reconstruct the positionality of the eschatological dimension within Reformed worship, in the end thereby synthesizing the Reformed eucharistic theology of Calvin with the Eastern Orthodox eucharistic theology articulated in Schmemann's thought in order to locate the eschatological-missionality of the Reformed liturgy. In the end, it is hoped that this constructive proposal might underscore the importance of the eucharistic aspect of the Reformed liturgy, even in such a way that emphasizes the very character of its eschatological-missionality.